STUDY OF STREPTOMYCES RECIFENSIS VAR. LYTICUS EXOMETABOLITES INFLUENCE ON THE GROWTH OF MUSHROOM PLEUROTUS OSTREATUS - О. М. Алєксєєнко; I. В. Жерносєкова; А. I. Вінніков (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2011)
Stimulating effect of cultural liquid of strains Streptomyces recifensis var. lyticus was shown relatively to the growth parameters of mushroom Pleurotus. ostreatus. Growth speed, colony diameter, the coefficient of growth of P. ostreatus was increased in the presence of streptomycetes strains exometabolites comparied with control.